COVID-19 VACCINATION OF SPONDYLOARTHRITIS PATIENTS RECEIVING BIOLOGICAL THERAPY: REAL-LIFE DATA - Yildirim, T. Demirci; Akleylek, C.; Cinakli, H.; Yildirim, D.; Hakbilen, S.; Coskun, B. N.; Onen, F. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK